2021
DOI: 10.1038/s41598-021-01580-0
|View full text |Cite|
|
Sign up to set email alerts
|

Prenatal exposure to persistent organic pollutants and metals and problematic child behavior at 3–5 years of age: a Greenlandic cohort study

Abstract: High levels of persistent organic pollutants (POPs) and heavy metals are found in Arctic populations. POP and heavy metals are linked to impaired cognitive development. This study examined associations between prenatal POP and metals exposure and problematic child behavior using the Strength and Difficulties Questionnaire (SDQ). POPs and metals were measured in 102 pregnant Greenlandic women. During follow-up at 3–5 years, parents answered an assisted questionnaire including children’s SDQ scores. Associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Similarly, in a Chinese study, maternal blood Cd concentrations were negatively associated with the social domain among 12 months old children (n = 300) (Wang et al 2016). Contrarily, Cd measured in maternal blood did not correlate with problematic behavior among 3-5 years old children from Greenland (n = 102) (Kornvig et al 2021). In a smaller study conducted on pregnant women of Arab-Bedouin origin (Karakis et al 2021), a link was observed between maternal concentrations of several metals, including Li, Co, Ni, Sr, V, As, Mo, and Cd and behavioral outcomes in the children at an age of 6 years (n = 111).…”
Section: Resultsmentioning
confidence: 85%
“…Similarly, in a Chinese study, maternal blood Cd concentrations were negatively associated with the social domain among 12 months old children (n = 300) (Wang et al 2016). Contrarily, Cd measured in maternal blood did not correlate with problematic behavior among 3-5 years old children from Greenland (n = 102) (Kornvig et al 2021). In a smaller study conducted on pregnant women of Arab-Bedouin origin (Karakis et al 2021), a link was observed between maternal concentrations of several metals, including Li, Co, Ni, Sr, V, As, Mo, and Cd and behavioral outcomes in the children at an age of 6 years (n = 111).…”
Section: Resultsmentioning
confidence: 85%
“…Additionally, prenatal serum PCBs were positively associated with abnormal scores for hyperactivity [37]. In contrast, earlier research found no links between prenatal exposure of PCBs and emotional or behavioral problems among children [16,38]. Meanwhile, it also has been demonstrated that prenatal dietary exposure to dioxins during pregnancy is not associated ADHD symptoms [39].…”
Section: Discussionmentioning
confidence: 85%
“…For instance, some studies have presented that prenatal exposure to metals is associated with autism, emotional control, hyperactivity/inattention, and depression among children [ 11 , 12 , 13 , 14 ]. However, researchers have also found that the association between prenatal metal exposure and autism is null [ 15 ] and the associations of persistent organic pollutants (POPs) and heavy metals with behavioral problems are inconsistent [ 16 ].…”
Section: Introductionmentioning
confidence: 99%